PERAN PEMBELAJARAN PAI DALAM MENCEGAH PERILAKU NEGATIF PADA ACARA KARNAVAL SOUND HOREG DAN MINUMAN KERAS DI GONDANGLEGI - Miftahul Huda; Muhammad Odik Arifin (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
The phenomenon of using loudspeakers and consuming alcoholic beverages at carnival events in Gondanglegi Subdistrict indicates a shift in values within society that has led to an increase in deviant behaviour among adolescents. This study aims to examine the role of Islamic Religious Education (PAI) in shaping students' character so that they do not fall into negative behaviour, especially in the context of carnival celebrations. The approach used in this study is qualitative with a case study method. Data collection techniques included observation, in-depth interviews, documentation, and focus group discussions. The results of the study show that PAI learning has a significant contribution in fostering students' morals and moral awareness. However, there are several obstacles that hinder the effective implementation of PAI, such as the lack of integration of learning with real life, weak parental supervision, and the negative influence of the social environment and digital media. As a solution, it is necessary to strengthen contextual learning methods, collaboration between schools, parents, and the community, as well as character building through applicable religious activities. Comprehensive and collaborative PAI learning has been proven to reduce deviant behaviour and increase religious awareness among students.